RETRACTED: Characteristics of clinical course and comorbidity formation of arterial hypotension in farmer population - Mamasoliev Ne’matjon; Tursunov J.H.; Nazarova Gulchekhra; Suleymanova Nasibakhon; Ergashbaeva Dilrabokhon (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001